Learning social studies via objects in museums: investigation into Turkish elementary school students' lived experiences - YILMAZ, ALİ; YILMAZ, KAYA (WILEY-BLACKWELL, 2013)
Based on a descriptive phenomenological research design, this study investigated Turkish elementary school students' experiences in learning social studies via objects in museums. After students visited four different museums during the teaching of three thematic units at sixth grade level, their lived experiences were elicited. Purposeful sampling was used to select the research participants and interviews were employed to gather data. The research data were analyzed by means of Giorgi's descriptive phenomenological framework, which helped reveal the structure of the phenomenon of learning social studies in museums. It was found that the essence of learning social studies via objects in museums consisted of five components. These were (1) excitement and motivation to learn about the past, (2) active participation in the learning process, (3) reconstruction of historical knowledge with the development of historical thinking skills, (4) enjoying social studies learning, and (5) heightened interest in social studies and seeing it as a valuable school subject. It was also found that some students had difficulties or negative learning experiences in their museum visits, such as difficulty in asking object-based questions or making comments on objects and relating them to the lessons being studied in the class. Because only a few students mentioned these difficulties, they were not included in the essence of the lived experience of learning social studies via objects in museums.
Keywords: PHENOMENOLOGY